The red pencil : convictions from experience in education - Sizer, Theodore R. (Yale University Press, 2004)
This engaging and important book is a critique of American education wrapped in a memoir. Drawing on his fifty years as teacher, principal, researcher, professor, and dean, Theodore R. Sizer identifies three crucial areas in which policy discussion about public education has been dangerously silent. He argues that we must break that silence and rethink how to educate our youth. Sizer discusses our failure to differentiate between teaching and learning, noting that formal schooling must adapt to and confront the powerful influences found outside traditional classrooms. He examines the practical as well as philosophical necessity for sharing policy-making authority among families, schools, and centralized governments. And he denounces our fetish with order, our belief that the familiar routines that have existed for generations are the only way to bring learning to children. Sizer provides alternatives to these failed routines - guidelines for creating a new educational system that would, among other things, break with wasteful traditional practice, utilize agencies and arrangements beyond the school building, and design each child's educational programme around his or her particular needs and potential.